A Phenomenological Study of the Experiences of Master’s Level Students of Color in Counseling Programs - Melanie Varney; Catherine Y Chang; Rafe McCullough; Mary Huffstead; Jennifer Smith (Teaching and Supervision in Counseling, 2019)
This qualitative study investigated the training experiences of 12 students of color in CACREP-accredited master’s level counseling programs using semi-structured phenomenological interviews. The 12 participants identified as Asian American (n = 2), Japanese American (n = 1), Chinese (n = 1), Black (n = 1), African American (n = 1), Latino and/or Hispanic (n = 3), and multiracial (n = 3). We used interpretive phenomenological analysis and identified three main themes: cultural marginalization; biculturalism; and safe or counter-hegemonic relationships. Training implications for counselor education programs are provided.
Keywords: students of color; biculturalism; training